Pengaruh Suhu dan Waktu Ekstraksi dalam Proses Pembuatan Pektin dari Kulit Buah Sukun dengan Pelarut Asam Sitrat - Rizka Nurlaila; Agam Muarif; Meriatna Meriatna; Masrullita Masrullita; Ishak Ishak (Journal of Science and Applicative Technology, 2023)
The breadfruit rinds has never been used, even though breadfruit rinds is known contain pectin which has a high economic value. Pectin is a biopolymer compound that functions as a water binder or liquid thickener obtained through the extraction process of fruits waste. The purpose of this research is to utilize the waste of breadfruit rinds into pectin to increase the economic value. This research used reflux extraction method with 7% citric acid as solvent, extraction time used was 170, 175,180, 185, and 190 minutes at 85, 90, and 95°C. The highest research results were obtained at a temperature of 95°C with a long extraction time of 195 minutes, namely yield of 40,762%, water content of 1,92%, methoxyl content of 8.06%, galacturonic content of 81%.